Chemical Constituents of Buah Makasar [Brucea Javanica (L) Merr] Leaves and Seed Extract - Handa Muliasari; Candra D Hamdin; Agus Dwi Ananto; Muhsinul Ihsan (Chemistry Education Program, the University of Mataram, 2019)
Buah Makasar [Brucea javanica (L) Merr] is one of the local plants in Lombok Island that is traditionally used for diabetic medication. The purpose of this research was to identify the chemical constituents containing in methanol leaves and seed extract of Buah Makasar. The methods used were phytochemical screening for some groups of chemical compounds and GC-MS analysis. The result of phytochemical screening showed that methanol extract of B. javanica seed contains alkaloids, terpenoids, and tannin with a high intensity; while the leaves extract contains alkaloids, flavonoids, steroids, tannin, and saponin. The differences of chemical compositions in the leaves and seed extract may give them have different bioactivities. GC-MS analysis showed some fatty acids containing in the seed extract such as stearic acid and palmitic acid.